2005
DOI: 10.1038/sj.bjp.0706087
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a signal peptide sequence to the α1D‐adrenoceptor gene increases the density of receptors, as determined by [3H]‐prazosin binding in the membranes

Abstract: 1 Both in mammalian tissues and in transfected cells, only low levels of a 1D -adrenoceptors are detected in radioligand binding studies. It has been implicated that the comparatively long N-terminal tail of the a 1D -adrenoceptor is responsible for the inefficient surface expression of the receptor. 2 In the present study, we created gene constructs for six N-terminally truncated variants of the human a 1D -adrenoceptor. These constructs were used to transfect Neuro2A cells. We show that the density of a 1D -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…It is interesting that we have found that the ␣ 1B -/␣ 1D -AR heterodimer is functionally similar to the GABA B receptor heterodimer. The ␣ 1B -AR serves to promote cell-surface expression of the ␣ 1D -AR (Hague et al, 2004c), possibly by masking an ER retention motif in the ␣ 1D -AR N terminus (Pupo et al, 2003;Hague et al, 2004a;Petrovska et al, 2005). In addition, it seems that within the ⌬12␣ 1B -AR/␣ 1D -AR heterodimer, the ⌬12␣ 1B -AR is primarily responsible for binding ligand, whereas the ␣ 1D -AR couples to G protein activation, but whether this is true for wild-type ␣ 1B -ARs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that we have found that the ␣ 1B -/␣ 1D -AR heterodimer is functionally similar to the GABA B receptor heterodimer. The ␣ 1B -AR serves to promote cell-surface expression of the ␣ 1D -AR (Hague et al, 2004c), possibly by masking an ER retention motif in the ␣ 1D -AR N terminus (Pupo et al, 2003;Hague et al, 2004a;Petrovska et al, 2005). In addition, it seems that within the ⌬12␣ 1B -AR/␣ 1D -AR heterodimer, the ⌬12␣ 1B -AR is primarily responsible for binding ligand, whereas the ␣ 1D -AR couples to G protein activation, but whether this is true for wild-type ␣ 1B -ARs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although presently there are no other GPCRs for which this evolved restriction of PME has been documented at the amino acid level, it is possible that this event may be more generally applicable in light of recent reports of other WT receptors that are also inefficiently expressed Uberti et al, 2005;Petrovska et al, 2005;Pietilä et al, 2005;Vandenberghe et al, 2005). It will be necessary to determine whether other proteins follow the same regulatory mechanism.…”
mentioning
confidence: 97%
“…Previous studies revealed truncating the proximal 79 amino acids of the NT liberates ADRA1D from intracellular clusters, facilitates trafficking to the plasma membrane, and enhances functional coupling in response to agonist stimulation (25)(26)(27). Although a useful experimental approach, no data existed suggesting the ADRA1D NT is subjected to post-translational proteolysis in situ or occurred under physiological contexts.…”
mentioning
confidence: 99%
“…As a control, the prototype NT ADRA1D mutant, ⌬1-79 ADRA1D, was included in the experimental protocol (Fig. 4B) to facilitate cross-analysis with previous ADRA1D NT studies (25)(26)(27). ␣ 1 -AR agonist efficacies are typically in the rank order of ADRA1A ADRA1B Ͼ ADRA1D in cell culture assays (35).…”
Section: Adra1d N-terminal Domain Is Endogenously Cleaved Inmentioning
confidence: 99%
See 1 more Smart Citation